Phytoextraction of Chromium from Contaminated Soil by Brassica juncea as Influenced by Chelating Agents - Ramprakash,; Kumari, Sachin; Sangwan, A.; Rajpaul,; Kumar, Sanjay (Asian Journal of Chemistry, 2013)
A pot experiment was conducted to evaluate the effect of amendments on phytoextraction of chromium using cyclohexanediaminotetraacetic acid, citric acid, diethylenetriamine-pentaacetic acid, nitrilotriacetic acid (at 3 mmol kg-1 soil) and farmyard manure (at 3 %) with Brassica juncea in the sewage sludge unamended and amended (at 3 %) soil. Application of chelating agents influenced dry matter yield and uptake of chromium by roots and shoots differentially depending upon the nature of the chelating agents. Dry matter yield of roots and shoots of Brassica juncea increased due to application of nitrilotriacetic acid, citric acid and farmyard manure whereas reverse trend was observed in cyclohexanediaminotetraacetic acid and diethylenetriamine-pentaacetic acid treated soils. Addition of sewage sludge at 3 % on dry weight basis was found beneficial in improving the plant growth. Chelating agents enhanced the chromium uptake by both roots and shoots and significantly higher values of chromiumuptake by roots and shoots were observed from amended as compared to sewage sludge unamended soil. Application of nitrilotriacetic acid was found more effective in enhancing the chromium uptake by Brassica juncea roots and shoots than any other chelating agents at both the growth stages. The chelating agents are found useful in enhancing phytoextractability of chromium by Brassica juncea. Hence, marginally chromium contaminated soil may be remediated by adding chelating agents.